2017
DOI: 10.1364/ol.42.000535
|View full text |Cite
|
Sign up to set email alerts
|

Electrical tunability due to coalescence of exceptional points in parity-time symmetric waveguides

Abstract: We demonstrate theoretically the electric tunability due to coalescence of exceptional points in PT-symmetric waveguides bounded by imperfect conductive layers. Owing to the competition effect of multimode interaction, multiple exceptional points and PT phase transitions could be attained in such a simple system and their occurrences are strongly dependent on the boundary conductive layers. When the conductive layers become very thin, it is found that the oblique transmittance and reflectance of the same syste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…It is worthy of noting that the occurrence of coalescence and rebifurcation of EPs shown above is attributed to the competition interacting effect among multiple states, which has also been discussed and analyzed in other multistate systems [19,21,22]. Remarkably, the external magnetic field applied on our proposed PT -symmetric waveguide could effectively tune the interaction among multiple states, but in a nonreciprocal manner, giving rise to the different evolution process between positive and negative guided modes.…”
Section: Nonreciprocal Exceptional Points and Phase Diagrammentioning
confidence: 52%
See 2 more Smart Citations
“…It is worthy of noting that the occurrence of coalescence and rebifurcation of EPs shown above is attributed to the competition interacting effect among multiple states, which has also been discussed and analyzed in other multistate systems [19,21,22]. Remarkably, the external magnetic field applied on our proposed PT -symmetric waveguide could effectively tune the interaction among multiple states, but in a nonreciprocal manner, giving rise to the different evolution process between positive and negative guided modes.…”
Section: Nonreciprocal Exceptional Points and Phase Diagrammentioning
confidence: 52%
“…Recently, more complex phenomena involved in the occurrence and evolution of EPs have been theoretically proposed and experimentally observed in PT -symmetric multistate systems [18][19][20][21][22][23][24][25][26][27][28]. For example, Alaeian and Dionne [18] demonstrated that in a five-layer plasmonic waveguide having PT symmetry, coalescence and evolution of EPs could be tuned to support positive or negative refractive indices by changing the coupling between the waveguide layers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the 𝒫𝒯 -symmetric mechanical system, 𝒫𝒯 -symmetric optical systems can produce extraordinary optical features and phenomena near the spontaneous 𝒫𝒯 -symmetric breaking point. Subsequently, 𝒫𝒯 -symmetric optical systems, such as 𝒫𝒯symmetric optical lattices, [6][7][8][9][10] optical waveguides, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] inhomogeneous nonlinear optical media, [30] and graphene, [31,32] have been widely investigated and some extraordinary optical characteristics, for instance, birefringence, [6] unidirec-tional invisibility, [8,9] ultrastrong absorption, [31] and singlemode lasing, [33,34] have been found.…”
Section: Introductionmentioning
confidence: 99%